(untitled) (Global Journal of Management and Business Research, 2021)
Trade union revitalisation does member commitment matter This is a million dollar question the study attempts to answer In this article the researcher reviews whether member commitment matters in trade union revitalisation The research equally determines the extent to which member commitment leads to trade union revitalisation through applying the ordinal least squares model to predict the relationship between member commitment and trade union revitalisation Findings reveal the existence a positive relationship between employee commitment and trade union revitalisation The researcher then develops a trade union revitalisation model based on the findings